If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 7) = 8 Reorder the terms: 5(7 + x) = 8 (7 * 5 + x * 5) = 8 (35 + 5x) = 8 Solving 35 + 5x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 5x = 8 + -35 Combine like terms: 35 + -35 = 0 0 + 5x = 8 + -35 5x = 8 + -35 Combine like terms: 8 + -35 = -27 5x = -27 Divide each side by '5'. x = -5.4 Simplifying x = -5.4
| 21Y-8Y(2)=6Y+1-10 | | 23-7+4(x-1)=11 | | 8y-3y+6=-10 | | x*.10=14.79 | | 27r^3+1=0 | | 19-2x-3=2x+6+x | | 7x-15=2x+10 | | 3x^2+7x+2=y | | 5x+12+6x=93+2x | | h=-10t^2+90 | | 3x-1=2x+2+1 | | 3x^3+25x^2+28x=0 | | 4(n+2)=9n-7 | | 2y-1+y=-2+13-2y | | x+y=-400 | | 4x+2x-60=48 | | 2p-10-2=12-p-p | | r^3+3r^2=0 | | v+1-2v=4 | | 3n+15=7n-1 | | 4+3n+2=-9 | | y=2cos(3x+1) | | -4=2x+x | | 4n+8=5n-2 | | 4*log(x-9)=3 | | -1+7x=-186 | | 7e^9t=11e^8t | | 15=-6n+3n | | -7r=-21 | | p+6=2 | | x^4-49x^2-360=0 | | y-8=4x |